The Impact of Large-Scale Continuing Professional Development on Teacher Professionalism in Indonesia and China: A Systematic Literature Review - Rokhmatul Khoiro Amin Putri; Kusaeri Kusaeri; Evi Fatimatur Rusdiyah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Continuous Professional Development (CPD) is vital for enhancing teaching quality and professional growth. This study compares the implementation and impact of CPD on teaching practices and teacher professionalism in Indonesia and China, highlighting similarities and differences in national strategies. A Systematic Literature Review (SLR) was conducted using the PRISMA protocol. Relevant literature was sourced from the Scopus database, following four stages: identification, screening, eligibility, and data extraction. From an initial pool of 735 articles, 17 met the inclusion criteria and were selected for in-depth analysis. Findings indicate a shift in Indonesia from traditional CPD models to more formalized systems, particularly through the Program Profesi Guru (PPG), which aims to improve teaching quality and align curricula with student needs. In China, CPD is embedded within national policy, notably through the National Teacher Training Program (NTTP), which emphasizes digital competencies and educational equity. Indonesian CPD initiatives have led to increased teacher motivation and improved instructional practices. In China, CPD efforts have enhanced teacher competence, reduced urban–rural disparities, and strengthened learning outcomes. Both countries have achieved positive outcomes through CPD, though their approaches differ. Indonesia prioritizes certification and curriculum relevance, while China focuses on policy integration and digital skills enhancement. CPD significantly contributes to teaching effectiveness and educational reform. While Indonesia emphasizes structured certification pathways, China’s approach integrates CPD into broader educational policies, underlining its strategic role in national development.